Carbon dioxide as a sustainable resource for macrocyclic oligourea. Issue 8 (11th January 2016) - Ying, Z.; Dong, Y.; Wang, J.; Yu, Y.; Zhou, Y.; Sun, Y.; Zhang, C.; Cheng, H.; Zhao, F.
Abstract : A macrocyclic polyurea oligomer was synthesized from a sustainable CO2 route. MALDI-TOF and tandem mass spectrometry were used to confirm the formation of macrocyclic polyurea oligomers via fragment analysis. Abstract : As carbon dioxide is an inexpensive, abundant, sustainable and green carbonyl resource, its utilization to produce value-added chemicals and polymeric materials has attracted much more attention. In this work, novel macrocyclic oligourea were synthesized and it is the first time to produce macrocyclic oligourea from a sustainable substrate of CO2 . The chemical composition and molecular structure of oligourea have been confirmed by FTIR, MALDI-TOF and tandem mass spectrometry. The formation of macrocyclic polyurea largely depends on the kind of solvent chosen and the reaction duration, which has been discussed according to the reaction phase behavior observation. The synthesized novel macrocyclic oligourea is expected to have important and special applications in the pharmaceutical industry. The present work provides a green and renewable process for the synthesis of a macrocyclic oligomer, which opens a new route for carbon dioxide utilization.